Integrative Analysis of the Doxorubicin-Associated LncRNA–mRNA Network Identifies Chemoresistance-Associated lnc-TRDMT1-5 as a Biomarker of Breast Cancer Progression - Chen, Qi; Yang, Hui; Zhu, Xiaolan; Xiong, Shangwan; Chi, Huamao; Xu, Wenlin (Frontiers in Genetics, 2020)
Increasing evidence has revealed close relationships between lncRNAs and chemoresistance in multiple types of tumors; however, functional lncRNAs in breast cancer have not been completely identified. In this study, we aimed to identify novel lncRNAs that might play critical roles in doxorubicn resistance, which could reveal potential biomarkers of breast cancer. Using a breast cancer dataset (GSE81971), we identified 452 lncRNAs that were upregulated and 659 that were downregulated; furthermore, there were 1896 differentially expressed mRNAs, of which 1137 were upregulated and 758 were downregulated in MCF-7/ADR cells compared with the expression in MCF-7 cells. We constructed an lncRNA-mRNA network by integrating probe reannotation and regulatory interactions. To elucidate the key lncRNAs in breast cancer, we further analyzed dysregulated lncRNA-mRNA crosstalk, and six candidate lncRNAs (lnc-TRDMT1-5, ZNF667-AS1, lnc-MPPE1-13, DSCAM-AS1:5, DSCAM-AS1:2, and lnc-CFI-3) were identified. Notably, the expression level of lnc-TRDMT1-5 was significantly upregulated in resistant cells compared with sensitive cells, and its levels were increased in breast cancer tissues compared with adjacent tissues. Levels were positively associated with ER and HER2 expression levels. High expression of lnc-TRDMT1-5 predicted poor prognosis in ER-positve and HER2-positive breast cancer patients, especially in patients with chemoresistance. Bioinformatic and functional analysis revealed that lnc-TRDMT1-5 was involved in many crucial pathways in cancer, such as the PI3K/AKT and Wnt signaling pathways. Subcellular localization predicted that lnc-TRDMT1-5 was located in the cytoplasm, and the lncRNA-miRNA-mRNA network showed that lnc-TRDMT1-5 might serve as a regulator in breast cancer. Here, our results demonstrated a dysregulated lncRNA-mRNA network that might provide new treatment strategies for chemoresistant breast cancer, and the results identified a new lncRNA, lnc-TRDMT1-5, with oncogenic and prognostic functions in human breast cancer.